Evaluation of 71 Coronary Artery Disease Risk Variants in a Multiethnic Cohort - Ke, Wangjing; Rand, Kristin A.; Conti, David V.; Setiawan, Veronica W.; Stram, Daniel O.; Wilkens, Lynne; Le Marchand, Loic; Assimes, Themistocles L.; Haiman, Christopher A. (Frontiers in Cardiovascular Medicine, 2018)
Background Coronary heart disease (CHD) is the most common cause of death worldwide. Previous studies have identified numerous common CHD susceptibility loci, with the vast majority identified in populations of European ancestry. How well these findings transfer to other racial/ethnic populations remains unclear. Methods and Results We examined the generalizability of the associations with 71 known CHD loci in African American, Latino and Japanese men and women in the Multiethnic Cohort (6,035 cases and 11,251 controls). In the combined multiethnic sample, 78% of the loci demonstrated odds ratios that were directionally consistent with those previously reported (p = 2 × 10−6), with this fraction ranging from 59% in Japanese to 70% in Latinos. The number of nominally significant associations across all susceptibility regions ranged from only 1 in Japanese to 11 in African Americans with the most statistically significant association observed through locus fine-mapping noted for rs3832016 (OR = 1.16, p = 2.5×10−5) in the SORT1 region on chromosome 1p13. Lastly, we examined the cumulative predictive effect of CHD SNPs across populations with improved power by creating genetic risk scores (GRSs) that summarize an individual’s aggregated exposure to risk variants. We found the GRSs to be significantly associated with risk in African Americans (OR = 1.03 per allele; p = 4.1×10−5) and Latinos (OR = 1.03; p = 2.2 × 10−8), but not in Japanese (OR = 1.01; p = 0.11). Conclusions While a sizable fraction of the known CHD loci appear to generalize in these populations, larger fine-mapping studies will be needed to localize the functional alleles and better define their contribution to CHD risk in these populations.